Clinical utility of direct application of matrix-assisted laser desorption ionization time-of-flight mass spectrometry and rapid disk diffusion test in presumptive antimicrobial therapy for bacteremia. Issue 11 (November 2018) - Magarifuchi, Hiroki; Hamada, Yohei; Oho, Megumi; Kusaba, Koji; Urakami, Toshiharu; Aoki, Yosuke
Abstract: Objective: To study how and to what degree the rapid pathogen identification by MALDI-TOF MS coupled with rapid disk diffusion test improve the current clinical practice of patients with bacteremia in a tertiary teaching hospital with full-time ID consultation service. Patients and methods: MALDI-TOF MS and 8H disk diffusion tests were directly applied to the positive blood cultures samples and the results were reflected on antimicrobial therapy (n = 119). The appropriateness of antimicrobial selection through these interventions was verified with conventional culture results in comparison with historical control (n = 129). The mortality of patients between the two periods was also compared. Results: The appropriateness of antimicrobial selection was higher (99.2%) in the intervention than in the control group (93.8%) (p 0.024), but there was no difference in 28-day mortality between the two periods (16.8%, 14.8%) (p 0.668). The duration of presumptive antimicrobial therapy with anti-MRSA agents and carbapenem antibiotics did not differ between the two periods indicating that the intervention was not effective in decreasing the unnecessary antibiotics. On the other hand, some bacteremic patients with pathogens whose drug susceptibilities were invariably sensitive to the standard class of antibiotics definitely benefitted from the intervention. Conclusion: The intervention utilizing MALDI-TOF MS and the rapid disk diffusion test may not demonstrate overall improvement in bacteremia mortality in the institution with full-time infectious disease consultants. Its utility has yet to be evaluated in different setting hospitals.